PENGARUH GAYA KEPEMIMPINAN DAN KONDISI FISIK TEMPAT KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Carlina, Astoeti (Universitas Pawyatan Daha, 2022)
condition, influence by simultan and partial of leadership style covering style leadership of task oriented and style leadership of relation oriented and also the condition of workplace physical of Pawyatan Daha Kediri to satisfaction of employees in institution of Pawyatan Daha Kediri and to know one of the dominant variable. This research is conducted to 40 teachers at school units in institution environment of Pawyatan Daha Kediri. Description of style leadership of task oriented and relation oriented and also the condition of institution physical of Pawyatan Daha Kediri can know to through spreading of guestionare to 40 teachers, then result from answer of guestionare the measured with Likert Scale. From result of data processing can be concluded that leadership style the applied is style leadership of relation oriented egual to:2,94 % as well as style leadership of task oriented egual :2,58 % and condition of unit physical units school in institution environment of Pawyatan Daha Kediri in a condtion goodness, egual to: 3,47 %. Based on analysis of regression doubled by simultan with test of F obtained by result of Sig F = 0,296 and value of signification T (sig t) X1 = 0,024, X2 = 0,031 and X3 = 0,035, the values smaller then real level (a = 0,05), its meaning style variable leadership of task oriented, style leadership of relation oriented and also the condition of institution physical of Pawyatan Daha Kediri have an effect on significan either through and also partial and simultan. Result of examination through determinant coerfficient (R2) obtained by result of R2 :0,16, its meaning that contribution given by leadership style variable and workplace physical condition to satisfaction of job egual to 16,5 % while 83,5 % influnced by other factor. Based on analysis of regression doubled by partial free variable wich most dominant influence variable tied is style variable leadership of task oriented with the smallest value of sigt : 0,024 and the biggest value of B = 0,383